Recovery time and heart rate variability following extreme endurance exercise in healthy women. Issue 21 (31st October 2018) - Gifford, Robert M.; Boos, Christopher J.; Reynolds, Rebecca M.; Woods, David R.
Abstract: The relationship between autonomic function and recovery following prolonged arduous exercise in women has not been examined. We undertook an exploratory study that aimed to examine the temporal change in linear and nonlinear measures of heart rate variability (HRV) following prolonged arduous exercise in the form of first all‐female (mean age 32.7 ± 3.1 years) team to attempt an unassisted Antarctic traverse. HRV analysis was performed before and 1, 4, and 15 days postexpedition. The traverse was completed in 61 days. There was a significant paired reduction in heart rate, LnLF, LF:HF, DFA α 1 between baseline and 15 days postexercise in the same environment. Conversely, RMSSD, LnHF and HFnu, SD1:SD2, and SampEn significantly increased. DFA α 2 levels significantly fell from baseline to Day 1 postexercise. In conclusion, we observed a significant latent increase in relative parasympathetic dominance and RR interval irregularity at 15 days post prolonged arduous exercise, versus pre‐exercise baseline, in a group of very fit and healthy adult women. Abstract : Heart rate variability was examined in eight women prior to and following a 61 day ultra‐endurance trans antarctic trek. We found that HRV and its complexity significantly increased versus baseline despite the intensity of the arduous exercise with no observed evidence of significant post expedition fatigue or maladaptive effects on autonomic function.